2020
DOI: 10.1037/trm0000193
|View full text |Cite
|
Sign up to set email alerts
|

Child trauma exposure and subsequent emotional functioning in El Salvador.

Abstract: This study examined the incidence of exposure to potentially traumatic life events and subsequent emotional functioning in Salvadorian children. Participants were 269 parents of youth aged 4 -17 who completed measures of child trauma exposure, posttraumatic stress disorder (PTSD) symptoms, emotional functioning, peer functioning, impairment, need for treatment, treatment preferences, and barriers to accessing treatment. More than half of Salvadorian children (57%) had been exposed to at least one potentially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
2
5
2
Order By: Relevance
“…Researchers have postulated that culturally, it is more acceptable for women and girls to express their emotions and endorse mental health difficulties than men and boys, and relatedly, that males have a higher likelihood of engaging in externalizing rather than internalizing behaviors following trauma exposure (Tolin & Foa, 2006). The finding that adolescents in the present study reported exposure to a higher number of traumatic event types and were more likely to have elevated scores on measures of PTSD, anxiety, and depression than children is also consistent with previous studies that have suggested older children are more likely to have a history of trauma exposure (Copeland et al., 2007; Johnco et al., 2020). Finally, consistent with other studies (Copeland et al., 2007; Johnco et al., 2020), we found evidence of a cumulative impact of trauma such that youth with higher levels of exposure to potentially traumatic events endorsed more severe symptoms of posttraumatic stress, anxiety, and depression.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Researchers have postulated that culturally, it is more acceptable for women and girls to express their emotions and endorse mental health difficulties than men and boys, and relatedly, that males have a higher likelihood of engaging in externalizing rather than internalizing behaviors following trauma exposure (Tolin & Foa, 2006). The finding that adolescents in the present study reported exposure to a higher number of traumatic event types and were more likely to have elevated scores on measures of PTSD, anxiety, and depression than children is also consistent with previous studies that have suggested older children are more likely to have a history of trauma exposure (Copeland et al., 2007; Johnco et al., 2020). Finally, consistent with other studies (Copeland et al., 2007; Johnco et al., 2020), we found evidence of a cumulative impact of trauma such that youth with higher levels of exposure to potentially traumatic events endorsed more severe symptoms of posttraumatic stress, anxiety, and depression.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that adolescents in the present study reported exposure to a higher number of traumatic event types and were more likely to have elevated scores on measures of PTSD, anxiety, and depression than children is also consistent with previous studies that have suggested older children are more likely to have a history of trauma exposure (Copeland et al., 2007; Johnco et al., 2020). Finally, consistent with other studies (Copeland et al., 2007; Johnco et al., 2020), we found evidence of a cumulative impact of trauma such that youth with higher levels of exposure to potentially traumatic events endorsed more severe symptoms of posttraumatic stress, anxiety, and depression.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations